A digital wallet experience evaluation using a Self-concept based method (Human Factors in Design, 2024)
The Self-concept method has the innovative feature of measuring the distance between the ideal and actual expectations, instead of considering the absolute grade received by an artifact. In this research, we used a method based on the Self-concept to evaluate the user experience of a digital wallet. Therefore, three prototypes of the same digital wallet application were evaluated using both the System Usability Scale (SUS) and the Self-concept-based methodology. Based on that, it was possible to define feelings/perceptions that qualify the experience with digital wallets and even evaluate successive versions of prototypes. The concept was considered less distant from the idealization of the test participants, and was generated insights based on users' experiences.
Keywords: user experience; UX/UI; Self-concept; design